Phlebotomine sand flies and Leishmania species in a focus of cutaneous leishmaniasis in Algeria. - Roumaissa Gherbi; Mustapha Bounechada; Maria Stefania Latrofa; Giada Annoscia; Viviana Domenica Tarallo; Filipe Dantas-Torres; Domenico Otranto (Public Library of Science (PLoS), 2020)
Cutaneous leishmaniasis is a disease caused by various Leishmania spp., which are transmitted by phlebotomine sand flies. Algeria is one of the most affected countries, with thousands of cutaneous leishmaniasis cases registered every year. From March to November of 2016 and 2017, sand flies were collected in 12 municipalities in Setif province, North-Eastern Algeria. Sand flies were identified and females were tested by PCR for detecting Leishmania DNA. Additionally, cutaneous leishmaniasis cases notified during the study period were analysed. Out of 1804 sand flies collected, 1737 were identified as belonging to seven species, with Phlebotomus perniciosus (76.2%), Ph. papatasi (16.7%) and Ph. sergenti (5.0%) being the most common species, representing together 97.9% of the collected specimens. The remaining specimens were identified as Sergentomyia minuta, Se. fallax, Ph. longicuspis and Ph. perfiliewi. The number of sand flies collected monthly was positively correlated with temperature. Out of 804 females tested, nine Ph. perniciosus (1.1%) scored positive for Leishmania infantum (n = 5), L. major (n = 3) and L. tropica (n = 1), respectively. During the study period, 34 cutaneous leishmaniasis cases were notified in Setif, of which 58.8% were patients residing in two urban and peri-urban municipalities and 41.2% in rural areas. The finding of Ph. perniciosus as the most abundant species in Setif suggests that this sand fly may be adapted to different biotopes in the North-East region of Algeria. The detection of different Leishmania spp. in Ph. perniciosus suggests a complex epidemiological picture of cutaneous leishmaniasis in Setif, with the involvement of different etiological agents and possibly with different reservoir hosts and vectors.